1999
DOI: 10.1109/68.766777
|View full text |Cite
|
Sign up to set email alerts
|

Push-pull fused vertical coupler switch

Abstract: Abstract-A single-electrode push-pull fused vertical coupler (FVC) switch using macroscopic crystal inversion symmetry is demonstrated. The anisotropic linear electrooptic effect in a zincblende crystal is used to achieve optical switching under 12-V reverse bias for a 6.9-mm-long FVC whose two guiding layers have different crystal symmetries. No switching is observed for the identical structure in which the two guiding layers have the same crystal symmetry.Index Terms-Electrooptic effects, optical directional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 10 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…With appropriate doping profile and material composition or orientation, one can control the change in the refractive index of different regions. For example Liu et al 5) have recently demonstrated push-pull operation for a vertical coupler switch with a use of a single electrode. This takes advantage of the anisotropic electrooptic effect in zinc-blende semiconductors.…”
Section: Simulation Results and Design Guidelinesmentioning
confidence: 99%
“…With appropriate doping profile and material composition or orientation, one can control the change in the refractive index of different regions. For example Liu et al 5) have recently demonstrated push-pull operation for a vertical coupler switch with a use of a single electrode. This takes advantage of the anisotropic electrooptic effect in zinc-blende semiconductors.…”
Section: Simulation Results and Design Guidelinesmentioning
confidence: 99%
“…Initially, an InP-InGaAsP vertical coupler switch that required a 12-V reverse bias for a 6.9-mm-long device was fabricated [16]. It was shown that switching at 12 V reverse bias for a 6.9-mm-long device could be achieved with a single electrode only when the crystal symmetry was inverted during fusion to achieve a push-pull configuration [14]. The cleaved facets and crystal orientations of the two configurations are shown in Fig.…”
Section: Other Devicesmentioning
confidence: 99%
“…Four-port devices were cascaded to make devices for more than two channels [12], [13]. Push-pull configuration optical switches [14] and devices of more than two layers [15] were also fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…By manipulating the appropriate doping profile, material composition, or orientation we can control the change in the refractive index of different regions to produce the asymmetric structure. For example, Liu et al recently demonstrated a push-pull operation for a vertical coupler switch with a single electrode [9]. Their operation took advan-…”
Section: Vertical Directional Coupler Switches With Sois Eras Amentioning
confidence: 99%